2015
DOI: 10.1002/cssc.201501320
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study on Ceramic Membranes for Low‐Cost Microbial Fuel Cells

Abstract: Microbial fuel cells (MFCs) made with different types of ceramic membranes were investigated to find a low‐cost alternative to commercially available proton exchange membranes. The MFCs operated with fresh human urine as the fuel. Pyrophyllite and earthenware produced the best performance to reach power densities of 6.93 and 6.85 W m−3, respectively, whereas mullite and alumina achieved power densities of 4.98 and 2.60 W m−3, respectively. The results indicate the dependence of bio‐film growth and activity on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(64 citation statements)
references
References 40 publications
2
61
0
1
Order By: Relevance
“…In previous studies, most of the metals removed have been reductively deposited rather than chemically precipitated on the cathode ,,, The separation of Sn, Fe and Cu metals on the electrodes of MFCs represents a challenge for the practical applications of this technology. However, here the metal deposits were mostly in the precipitates for the Sn and Fe metals (82±5% in MFC Sn ; 89±4% in MFC Fe ).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, most of the metals removed have been reductively deposited rather than chemically precipitated on the cathode ,,, The separation of Sn, Fe and Cu metals on the electrodes of MFCs represents a challenge for the practical applications of this technology. However, here the metal deposits were mostly in the precipitates for the Sn and Fe metals (82±5% in MFC Sn ; 89±4% in MFC Fe ).…”
Section: Resultsmentioning
confidence: 99%
“…Different types of ceramic materials have been tested within MFC systems including terracotta, earthenware, mullite, pyrophyllite and alumina . These MFCs were fed with a mixture of urine and activated sludge.…”
Section: Bioelectrochemical Systems Fed With Urinementioning
confidence: 99%
“…For instance, a comparison of the iron‐rich terracotta with an open porosity of 9.1 % and earthenware with an open porosity of 16.6 % showed that the less dense earthenware material generated higher power output, meaning that porosity plays the major role. A similar study which compared power outputs by various ceramic materials including earthenware, pyrophyllite, mullite and alumina showed that pyrophyllite and earthenware gave the best performance with power densities of 6.93 and 6.85 Wm −3 , respectively, whilst mullite and alumina produced lower power densities of 4.98 and 2.6 Wm −3 , respectively . The impact of the wall thickness of fine fire clay on power output and catholyte generation was evaluated by Merino Jimenez et al .…”
Section: Bioelectrochemical Systems Fed With Urinementioning
confidence: 99%
“…Therefore, inexpensive membranes such as nylon filter, glass fiber mat, and non-woven cloth have been reported [61]. Pasternak et al [62] compared the performance of different kinds of ceramic membranes (alumina, earthenware, mullite, and pyrophyllite), and evaluated their characteristics in a cascade of MFCs. Pyrophyllite yielded the best performance for the MFCs and achieved a power density of 6.93 mW/m 2 [62], wherein the chemical properties of the ceramic membranes affect the cell performance.…”
Section: Microbial Fuel Cellmentioning
confidence: 99%